Tożsamość narodowa mieszkańców Wielkiego Księstwa Poznańskiego - Kanafocka, Patrycja (Studia Europaea Gnesnensia, 2010)
The article undertakes the issue of struggle for national identity on the territories of the Prussian partition. In the Grand Duchy of Poznań, intelligentsia was the main-stay of patriotism, who chose to engage in organic work, especially after the January Uprising. The author presents the endeavours of the Greater Poland landowners and clergy, which aimed at preserving Polish national identity